2010
DOI: 10.1261/rna.2197210
|View full text |Cite
|
Sign up to set email alerts
|

The HCV IRES pseudoknot positions the initiation codon on the 40S ribosomal subunit

Abstract: The hepatitis C virus (HCV) genomic RNA contains an internal ribosome entry site (IRES) in its 59 untranslated region, the structure of which is essential for viral protein translation. The IRES includes a predicted pseudoknot interaction near the AUG start codon, but the results of previous studies of its structure have been conflicting. Using mutational analysis coupled with activity and functional assays, we verified the importance of pseudoknot base pairings for IRES-mediated translation and, using 35 muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 36 publications
5
93
0
Order By: Relevance
“…The potential correlation between structural features of both RNAs and reactivity toward OPWRu was also analyzed (Supplemental Tables 2, 3). We could not conclude that there is a direct correlation among the OPW-Ru reactivity and any of the structural features (solvent accessibility measured by OH-radical reactivity in both the HCV and FMDV IRES elements [Kieft et al 1999;Lozano et al 2014]; and interacting edges, sugar conformation, or backbone turn in the case of the HCV IRES element [Kieft et al 2002;Lukavsky et al 2003;Berry et al 2010;Perard et al 2013]). Concerning the type of secondary structure motif, a preferential attack to positions present in four-way junctions was observed (Figs.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The potential correlation between structural features of both RNAs and reactivity toward OPWRu was also analyzed (Supplemental Tables 2, 3). We could not conclude that there is a direct correlation among the OPW-Ru reactivity and any of the structural features (solvent accessibility measured by OH-radical reactivity in both the HCV and FMDV IRES elements [Kieft et al 1999;Lozano et al 2014]; and interacting edges, sugar conformation, or backbone turn in the case of the HCV IRES element [Kieft et al 2002;Lukavsky et al 2003;Berry et al 2010;Perard et al 2013]). Concerning the type of secondary structure motif, a preferential attack to positions present in four-way junctions was observed (Figs.…”
Section: Resultsmentioning
confidence: 86%
“…To reinforce these results and provide further support to the validity of this compound for RNA structural analysis, we investigated the reactivity of a different RNA molecule for which three-dimensional structure has been determined using different approaches alone or in complex with the 80S ribosome (Lukavsky et al 2000(Lukavsky et al , 2003Kieft et al 2002;Melcher et al 2003;Easton et al 2009;Berry et al 2010;Perard et al 2013;Quade et al 2015). To this end, the reactivity of the hepatitis C virus (HCV) IRES toward OPW-Ru was analyzed in parallel to NMIA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for this is found in our toeprinting assays of WT and mutant IRESd40S complexes. In addition, recent biochemical and modeling studies report that the pseudoknot structure upstream of dIV plays a role in properly positioning the start codon in the P-site (Berry et al 2010;Lavender et al 2010) and, thus, there is a precedent for the structure of RNA upstream of the HCV AUG affecting its location. However, Locker et al (2007) showed by crosslinking that complete removal of dII (mutant DdII) does not appear to affect the AUG-tRNA anticodon interaction in the P-site (Locker et al 2007) (although there are some alterations to the toeprint).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoknots are present in ribozymes (Ferre-D'Amare et al 1998;Baskerville and Bartel 2002) and telomerases (ten Dam et al 1991;Bhattacharyya and Blackburn 1994;Comolli et al 2002). They have been shown to be important for the internal ribosome entry site (IRES) and initiation of translation (Kanamori and Nakashima 2001;Berry et al 2010) as well as in autoregulation (Benard et al 1998) and frame-shifting (Giedroc et al 2000;Theis et al 2008;Giedroc and Cornish 2009). Kissing loops are specific examples of pseudoknots in which two loops form intermolecular interactions, for example, in HIV-1 replication (for review, see Lu et al 2011).…”
Section: Introductionmentioning
confidence: 99%